Economic of Adaptation to Climate Change : Bangladesh, Volume 1. Main Report - World Bank (Washington, DC, 2013)
Bangladesh is one of the most vulnerable countries in the world to climate risks. Two-thirds of the nation is less than 5 meters above sea level and is susceptible to river and rainwater flooding, particularly during the monsoon. The Bangladesh Climate Change Strategy and Action Plan (BCCSAP), adopted by the government of Bangladesh in 2009, seek to guide activities and programs related to climate change in Bangladesh. Until the past few years, climatic risks have been poorly reflected in national policies and programs Bangladesh. The objective of this study is to help decision makers in Bangladesh to better understand and assess the risks posed by climate change and to better design strategies to adapt to climate change. The study takes as its starting point the BCCSAP. It builds upon and strengthens the analytical models and quantitative assessment tools already in use in Bangladesh in support of the research and knowledge management theme of BCCSAP. The scope of this study is more limited than the BCCSAP, so the reported costs represent a lower bound on the total adaptation costs in Bangladesh. The study was developed in four discrete and somewhat independent components with varying degrees of analytical depth and quantification.